INFLUENCE OF SERVICE QUALITY AND OPERATIONAL STANDARD OF SERVICE PROCEDURES (SOP) ON SATISFACTION OF COMMUNITY AT ONE-STOP SERVICE IMPLEMENTING UNIT SUB DISTRICT GUNUNG SAHARI UTARA - Tuswoyo; Kartika Methasari (JILPR Journal Indonesia Law and Policy Review, 2022)
The purpose of this research is to know the influence of service quality and operational standard of service procedures (SOP) to public satisfaction at One-Stop Service Implementing Unit Sub District Gunung Sahari Utara. This research is a quantitative field research. Field research is a study to obtain data that actually occurs in the field. While quantitative means to emphasize the analysis of numerical data (numbers) obtained by statistical methods. The method used in this research is Survey research method. The population in this study were all applicants who used the services of One-Stop Service Implementing Unit Sub District Gunung Sahari Utara, taken based on the average number of visitors per month (period September - October 2017). So the sample in this study is as many as 271 people. The sampling technique used in this research is convenience/accidental sampling. Based on the result of F test analysis known that the value of F count 41.304, and with the level of significance (p-value), 0.000. This means that the value of Sig<value of (0.000 < 0.05), it can be concluded that Service Quality (X1) and Standard Operational Procedure Service (X2) together have a very significant effect on Satisfaction of society (Y). The result of Determination Coefficient analysis is known that the influence between Quality of service (X1) and Standard Operational Procedure Service (X2) on Satisfaction of society (Y) obtained coefficient of determination equal to 0.236. This implies that about 23.6% of the variations occurring in Community Satisfaction in the One-Stop Service Implementing Unit Sub District Gunung Sahari Utara can be explained by Quality of Service and Standard Operational Procedure of Service.